The Effect of Cooperative Script Metacognitive Learning Model (CSM) on Cognitive Ability of Class X Students at SMAN 1 Cibadak - Hasanah, Iswati; Ramdhan, Billyardi; Rustandi, Eris (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2022)
Background: This research is entitled The Effect of Cooperative Script Metacognitive Learning Model (CSM) on Students' Cognitive Ability at SMAN 1 Cibadak. Thesis, Department of Biology Education, Faculty of Teacher Training and Education, University of Muhammadiyah Sukabumi, 2013. The purpose of this study was to determine the effect of the application of the CSM learning model on students' cognitive abilities. Methods: The method used in this research was quasi-experimental method with research design of Nonequivalent Control Group Design. This research was conducted at SMAN 1 Cibadak in the academic year 2012/2013. Sampling technique in this study used purposive sampling. Two classes from seven classes of X grade students. One class received learning with CSM model as the experimental group and one class received learning with Cooperative Learning model as the control class. The research subjects totaled 75 students, 38 students in the experimental class and 37 students in the control class. The instrument used to collect data in this study was a multiple choice test in accordance with the cognitive indicators of biology on environmental pollution material. Results: The results of this study indicate that the CSM learning model has an effect on students' cognitive abilities significantly, seen from hypothesis testing using t-test calculations, obtained tcount = 3.83 and ttable of 1.99 with a significance level (α) = 0.05 and degrees of freedom 73. Because tcount> ttable, so H0 is rejected and H1 is accepted. Conclusion: Based on the results of the analysis of the difference in the average score of student learning outcomes at each cognitive level, it shows that the application of the CSM learning model has a significant effect on students' cognitive abilities. Keywords : Cooperative Script Metacognitive, cognitive ability